2011
DOI: 10.1017/s0021932011000678
|View full text |Cite
|
Sign up to set email alerts
|

The Challenges of Offering Public Second Trimester Abortion Services in South Africa: Health Care Providers' Perspectives

Abstract: Around 25% of abortions in South Africa are performed in the second trimester. This study aimed to better understand what doctors, nurses and hospital managers involved in second trimester abortion care thought about these services and how they could be improved. Nineteen in-depth interviews with abortion-related service providers and managers in the Western Cape Province, South Africa, were undertaken. Data were analysed using a thematic analysis approach. Participants expressed resistance to the dilation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
50
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(52 citation statements)
references
References 17 publications
1
50
1
Order By: Relevance
“…This rate is close to that found in South Africa where 25% of abortions were STA [11], but higher than figures for USA in 2008 which revealed that 10.3% of abortions were STA with only 4% at 16 weeks and above [10]. The limit between the first and the second trimesters varies from 12 to 13 weeks according to authors.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…This rate is close to that found in South Africa where 25% of abortions were STA [11], but higher than figures for USA in 2008 which revealed that 10.3% of abortions were STA with only 4% at 16 weeks and above [10]. The limit between the first and the second trimesters varies from 12 to 13 weeks according to authors.…”
Section: Discussionsupporting
confidence: 82%
“…In the past two decades, misoprostol has been very effective in terminating pregnancy at various gestational ages [19]. Misoprostol is still the drug of choice for terminating pregnancy in the second trimester in other studies [11,19]. In our series, misoprostol was not commonly used in terminating STA.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Difficulties in access to safe TOP services add to HIV and obstetric causes of maternal mortality [11]. The factors that have influenced access to TOP services include: negative attitudes towards TOP services and the staff who provide TOP services; poor infrastructure; staff shortages and lack of support programmes for the few health care providers in existing TOP services [12,13]. …”
Section: Introductionmentioning
confidence: 99%